2011
DOI: 10.1002/stc.434
|View full text |Cite
|
Sign up to set email alerts
|

Parametric identification of the Dahl model for large scale MR dampers

Abstract: SUMMARY Magnetorheological (MR) dampers are promising control devices in civil engineering structures as they combine reliability and stability of passive systems while maintaining versatility of active devices without large power requirements. These dampers are intrinsically nonlinear, so one of the challenging aspects of applying this technology is the development of accurate models to describe their behaviour for control design and evaluation purposes. This paper deals with the parametric identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 22 publications
3
43
0
2
Order By: Relevance
“…Aguirre et al . have demonstrated that the forces predicted using the viscous + Dahl model were in good agreement with experimental results. Xu et al .…”
Section: Effective Damper Locationssupporting
confidence: 64%
See 1 more Smart Citation
“…Aguirre et al . have demonstrated that the forces predicted using the viscous + Dahl model were in good agreement with experimental results. Xu et al .…”
Section: Effective Damper Locationssupporting
confidence: 64%
“…Therefore, using them required the development of accurate models, allowing proper description of their behavior for control design and evaluation purposes. Aguirre et al [26] have demonstrated that the forces predicted using the viscous + Dahl model were in good agreement with experimental results. Xu et al [18] have reported that a modified sigmoid model accurately describes the behaviors of MR devices.…”
Section: Effective Damper Locationsmentioning
confidence: 65%
“…In the parametric models, physical quantities such as viscosity and friction are utilized to determine the dynamic behaviour of the damper. Classical approaches of this kind include (i) the Bingham model [27], (ii) the Bouc-Wen model [18,28], (iii) the hyperbolic tangent model [29] and (iv) the Dahl friction model [30,31]. Nonparametric models utilize soft computing methods such as fuzzy logic and neural networks to describe the dynamic behaviour of the damper, typically on the basis of some experimental tuning.…”
Section: Semi-active Control Of Structures With Mr Dampersmentioning
confidence: 99%
“…Furthermore, experimental works on parameter identification of MR dampers showed that the parameters α, k 0 , and c 0 are not always related to input current through linear equations as given in Eqs ()–(), but quadratic or cubic relations are better identified for large‐scale MR dampers . However, the nonlinear description of these parameters is also easily applicable for direct controller to find the optimal input voltage.…”
Section: Direct Controller Designmentioning
confidence: 99%